The Macmillan visual dictionary - Archambault, Ariane; Corbeil, Jean Claude (New York : Macmillan : Maxwell Macmillan International, 1992)
Comprehensive visual dictionary in full color covering 600 subjects and identifying more than 25,000 terms by the use of thousands of illustrations.
Includes index.
Library Journal
School Library Journal
Wilson's Senior High School
Adult.
Adult
Keywords: Handbooks, vade-mecums, etc; Picture dictionaries, English; Handbooks, manuals, etc; Picture dictionaries, English